Winckelmann-Gesellschaft, e.V. Winckelmann-Museum - Winckelmann-Gesellschaft (2006)
[Dt.:] Informationen rund um die Winckelmann-Gesellschaft sowie das Winckelmann-Museum (Ziele, Sammlungen, Publikationen, Organisation). Die Dauerausstellung informiert über Leben und Werk des berühmten Archäologen. Das Museum verfügt auch über eine kleine Sammlung aus antiken Originalen, die Ende der 70er Jahre von dem Schriftsteller Heinrich Alexander Stoll übereignet wurde. [Engl.:] Information about Johann Joachim Winckelmann, the Winckelmann Society (goals, history, publications, organisation). The second part introduces into the museum of the same name and its exhibitions. It was build at the birthplace of the researcher Winckelmann, in Stendal. The permanent exhibition explains life and work of the archaeologist Winckelmann. The museum also houses a small collection of original Ancient works of art, which were assigned by the writer Heinrich Alexander Stoll in the 70s.